Developing High School Mathematics Teacher Competence Through Computational Thinking Integration Workshop - Sari, Delsika Pramata; Pamuji, Rizky; Purba, Harja Santana; Adini, Muhammad Hifdzi; Saputra, Novan Alkaf Bahraini; Sukmawati, R Ati; Wiranda, Nuruddin; Mahardika, Andi Ichsan; Alizhafya, Nova Nor; Ardhabilly, Muchammad (Universitas Lambung Mangkurat, 2025)
This community service (CS) aimed to develop the competence of high school mathematics teachers through workshops integrating computational thinking in Barito Kuala Regency. The implementation method of this consisted of preparation, activity implementation and mentoring, and evaluation stages. In the preparation stage, a computational thinking workshop module was developed for mathematics material and distributed to participants during the training activities. Community service with a Participatory Action Research (PAR) approach is oriented towards community empowerment so the community can become an actor of change. Community service activities facilitate bridging mathematics teachers to develop CT in this case. This CS activity was conducted over two face-to-face meetings from August to September 2024. This CS activity was implemented in the Global Islamic Boarding School (GIBS) computer laboratory in Barito Kuala Regency. The participants who attended were 54 high school mathematics teachers from the region. The evaluation instrument used for data collection was a questionnaire filled out by participants via Google Forms. After the workshop, The evaluation showed that most teachers understood that CT was related to problem-solving through a systematic, logical, and algorithm-based approach. The high average score indicated that the training provided successfully introduced and effectively explained the CT concept. The involvement and active participation of teachers were very evident in this activity. Furthermore, an interesting finding was that teachers expressed 89.8% agreement that computational thinking needed to be taught to students. This was because CT could help students think critically and logically and build mental resilience, thereby increasing their readiness for the world of work in the future.